Clade age and diversification rate variation explain disparity in species richness among water scavenger beetle (Hydrophilidae) lineages - Bloom, Devin D; Fikáček, Martin; Short, Andrew E Z (PloS one, 2014)
Explaining the disparity of species richness across the tree of life is one of the great challenges in evolutionary biology. Some lineages are exceptionally species rich, while others are relatively species poor. One explanation for heterogeneity among clade richness is that older clades are more species rich because they have had more time to accrue diversity than younger clades. Alternatively, disparity in species richness may be due to among-lineage diversification rate variation. Here we investigate diversification in water scavenger beetles (Hydrophilidae), which vary in species richness among major lineages by as much as 20 fold. Using a time-calibrated phylogeny and comparative methods, we test for a relationship between clade age and species richness and for shifts in diversification rate in hydrophilids. We detected a single diversification rate increase in Megasternini, a relatively young and species rich clade whose diversity might be explained by the stunning diversity of ecological niches occupied by this clade. We find that Amphiopini, an old clade, is significantly more species poor than expected, possibly due to its restricted geographic range. The remaining lineages show a correlation between species richness and clade age, suggesting that both clade age and variation in diversification rates explain the disparity in species richness in hydrophilids. We find little evidence that transitions between aquatic, semiaquatic, and terrestrial habitats are linked to shifts in diversification rates.
Keywords: Animals; Phylogeny; brouci; biodiverzita; zvířata; fylogeneze; Coleoptera; Biodiversity